Palaeohydrology of the Siwalik Group along the Bakiya Khola section, central Nepal Himalaya (Journal of Nepal Geological Society, 2002)
Middle Miocene to Early Pleistocene fluvial sediments of the Siwalik Group comprises many fining-upward cycles from several to tens of metres thick. It is a foreland basin sediment with a coarsening-upward succession as a whole. The palaeohydrology and evolution of the fluvial depositional system of the group in the Bakiya Khola section of central Nepal was established using the grain size analyses, sedimentary structures and thickness of fining-upward cycles. Stratigraphically from older to younger sequence, the velocity and channel gradient of the palaeofluvial system varies from 0.28 m/s to 3.3 m/s and 2.9x10-5 to 3.4x10-4 m/m, respectively. The progressive changes in palaeovelocity and palaeochannel gradient reflect the southward propagation of thrust activities in the Himalayan front.